Penerapan Model PBL Berbantuan Software Geogebra Terhadap Kemampuan Pemecahan Masalah Matematis Pada Materi Persamaan Lingkaran - Aulya, Muhammad Rico; Purwati, Heni; Wardani, Bayu; Muhtarom, Muhtarom (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to investigate whether students' mathematical problem solving skills can improve when using the problem-based learning (PBL) model with the help of Geogebra software on circle equation material. The research method uses quasi-experiment or quasi-experiment which in its implementation uses two research subjects, namely the experimental group class and the control group class. The research population was class XI students of SMK N 7 Semarang. The samples used were 2 classes, namely class XI KGS 1 (experimental group) and class XI TME 1 (control group). The data collection method was carried out using test instruments and non-test instruments. Pretest and posttest assessments were used to collect data. Based on the findings of the Mann Whitney and Wilcoxon tests which display a sig value of 0.000 < 0.05 when using SPSS. If Ha is accepted and Ho is rejected. So the results of the Wilcoxon test and Mann Whitney test can be concluded that the PBL teaching approach has an impact on several students of SMK N 7 Semarang class XI in their mathematical problem solving abilities.